Examining the Predictors of Turnover Behavior in Newly Employed Certified Nurse Aides: A Prospective Cohort Study - Hsiao-Ching Chen; Jiun-Yi Wang; Ya-Chen Lee; Shang-Yu Yang (Elsevier, 2023)
Background: The turnover rate of nurse aides in Taiwan is high. However, the predictors of turnover behavior in the newly employed are still unclear. Objective: To examine the predictors of turnover behavior in newly employed licensed nurse aides. Methods: A longitudinal study design was used and subjects were newly employed certified nurse aides from a nurse aid training association in Taiwan. A total of five questionnaire surveys were conducted. The questionnaire was mainly used to collect information on turnover behavior, personal socioeconomic background, workplace psychosocial hazards, worker health hazards, and musculoskeletal disorders. Results: A total of 300 participants were recruited in the study. Cox regression analysis results showed that short working experience (hazard ratio [HR] = 0.21, p < 0.01), work as non-home nurse aides (HR = 0.58, p = 0.01), low monthly salary (HR = 0.68, p < 0.01), high work mental load (HR = 1.01, p = 0.01), low workplace justice (HR = 0.97, p < 0.01), high workplace violence (HR = 1.60, p < 0.01), high burnout (HR = 1.01, p = 0.04), poor mental health (HR = 1.06, p = 0.04), and high total number of musculoskeletal disorder sites (HR = 1.08, p = 0.01) contribute to a higher risk of turnover. Conclusion: The results indicated that employment period, work as a home nurse aide, monthly salary, work mental load, workplace justice, workplace violence, work-related burnout, mental health, and total number of musculoskeletal disorder sites are predictors of turnover behavior in newly employed certified nurse aides.